Monoclonal antibodies : a practical approach - Shepherd, Philip; Dean, Christopher (Christopher J.) (Practical approach series., 2000)
Monoclonal Antibodies: A Practical Approach deals with the preparation, testing, derivation, and applications of monoclonal antibodies. It will be an invaluable laboratory bench companion to both new and experienced immunologists.